Effect of maternal age and gestational weight gain on anthropometry of the newborn in semi urban area of Chhattisgarh, India - Motwani, Naresh P.; Jain, Ankit; C., Sudhakar (International Journal of Contemporary Pediatrics, 2019)
Background: Maternal undernutrition is a known to be a major factor contributing to adverse pregnancy outcomes. Gestational weight gain and young maternal age at childbearing years is associated with an increased risk low birth weight babies and infant mortality. Methods: Prospective observational study carried out in the post-natal ward of a tertiary care hospital (CM hospital) in a semi-urban area over a period of 1 year in between March 2018 and March 2019. Total 150 mothers who satisfied the inclusion criteria were enrolled. Age of the mothers was noted and were divided into 5 groups. Last known pre-pregnancy weight was recorded on re-call basis, recorded data on first visit during first month of pregnancy and again they were weighed in the third trimester at the time of admission using standard electronic weight machine. Data collected were entered in Microsoft Excel Work sheet 2018 which was imported to SPSS (version16) for data analysis. Quantitative data has been analysed by Mean, Standard deviation, T test and Karl Pearson correlation. Results: Mean birth weight among young age mother (<20 years) was 2068 g (95%CI,±223.99) which was significantly lower than mean birth weight of 20-30 year old mother (271.19 g±95%CI, 437.02) and >30 year old mother (2932.78, 95%CI±429.99). With increase in gestational weight gain there was a corresponding increase in mean birth weight and this increase was statistically significant (r=0.435, p=<0.001). Conclusions: Maternal age and gestational weight gain had significant impact on new-born anthropometry. Young age (<20yrs) and decreased gestational weight gain is associated with increased number of low birth weight babies.